Study of Mid-Infrared Emission and Structural Properties of Heavy Metal Oxide Glass and Optical Fibre Co-Doped with Ho(3+)/Yb(3+) Ions - Ragin, Tomasz (Materials (Basel), 2019)
Bismuth-germanate glasses with low hydroxide content co-doped with Ho(3+)/Yb(3+) ions have been investigated in terms of structural and spectroscopic properties. To reduce OH(-) ions content and improve transmittance value at the wavelength of 3.1 µm, the glass synthesis has been carried out in low vacuum conditions (45–65 mBar). The composition of the host glass based on heavy metal oxides affects the maximum phonon energy (hω(max) = 724 cm(−1)), which low value has a positive impact on the mid-infrared emission parameters. Emission band at the wavelength of 2.87 µm was observed in glass co-doped with mol% 0.25 Ho(2)O(3)/0.75 Yb(2)O(3) under 980 nm high power laser diode wavelength excitation. Lifetime measurements of the Yb(3+):(2)F(5/2) quantum level indicate efficient Yb(3+) → Ho(3+) energy transfer (η = 61%). The developed active bismuth-germanate glass was used as the core of optical fibre operating in the mid-infrared region.